AKTIFITAS PEMUPUKAN FOSFOR (P) PADA LAHAN SAWAH DENGAN KANDUNGAN P-SEDANG - Yulinar Zubaidah; Rafli Munir (Jurnal Solum, 2007)
This experiment was conducted at famer’s field in Kasang, Padang Pariaman Regency from July to November 2000. The experiment was designed in a randomized block design (RBD) with the treatment was five levels of SP36 fertilizer ( 0, 50, 75, 100, and 125 Kg/ha) and P starter (20 kg SP36/ha) with three replications. The results showed that the plant height was not affected by application of P fertilizer. Increasing P application tended to increase yield of rice. Application of 125 Kg SP36/ha gave the highest grain yield 7,6 ton/ha.Keywords: Soil P-Status, Rice field, P-fertilizer